Sistem Pendukung Keputusan Seleksi Pendidikan dan Pengembangan Pegawai Negeri dengan Metode AHP dan SAW - Fadhil Muhammad Supriyanto; Agung Triayudi; Ira Diana Sholihati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Education in Staff Operation of Indonesian National Police is an important element that aims to improve the quality of personnel. Staff Operation of Indonesian National Police (Sops Polri) is an unit in the National Police of Indonesian Headquarters. Education and development is carried out by the Staff Human Resources of Indonesian National Police (SSDM Polri) by gathering personnel data from various units. At first Sops Polri has to select its personnel so that the selected personnel is the best. But the process of selection in Sops Polri still done manually and the chances of errors are very large. So the development of decision support system using AHP and SAW methods can help the process of selection in Sops Polri. After decision support system was developed then it was tested by using the System Usability Scale (SUS) method with a result of 80.25 which can be interpreted as acceptable.